Analysis of Students Creative Thinking Abilities on the Topic of Energy in Living Systems - Hulinggato, Asrawati; Pikoli, Masrid; Uloli, Ritin (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Creative thinking is a habit of sharp thinking with intuition, moving the imagination, revealing new possibilities, uncovering unique ideas, and inspiring unexpected ideas. Based on fluency, flexibility, and originality, this research aims to describe students' creative thinking abilities regarding energy material in class VII life systems at SMP Negeri 1 Tapa. This research type is descriptive qualitative research. The instrument used is a 10-number essay test whose validity has been tested. The sample used in this research was 30 students. The results of research on creative thinking abilities on energy materials in living systems are in the fluency aspect of 55.83% in the enough creative category, the flexibility aspect of 67.5% in the creative category, and the originality aspect of 52.5% in the enough creative category. This shows that the low ability to think creatively is due to students' need to understand the creative thinking ability test and students' unfamiliarity with creative thinking. Students are expected to be able to practice working on questions that can hone creative thinking skills and can use the results of this research as a reference for further research related to creative thinking skills.